Scientific Reasoning in Problem-Based Distance Learning with the help of Edmodo on Wave Topic - Fitroh Fuadah; Lia Yuliati; Parno Parno (Jurnal Pendidikan Sains, 2021)
Abstract: Scientific reasoning ability is the ability to complete the results of an investigation. The purpose of this study was to analyze the ability of scientific reasoning in problem-based distance learning assisted by Edmodo. The design of this research is implanted experimental. Subjects of this research were 70 students of class XI MIPA SMAN 2 Jember. The instrument was used in the form of 4 essay questions. The n-gain value of the experimental class was 0.795 (high), the control class was 0.313 (medium). While the effect size of the experimental class is 3.28 (strong) and the control is 1 (enough). This shows that problem-based distance learning assisted by Edmodo has a strong effect on students' reasoning abilities on wave material.Abstrak: Kemampuan penalaran ilmiah merupakan kemampuan untuk menafsirkan hasil dari sebuah penyelidikan. Tujuan penelitian ini untuk menganalisis kemampuan penalaran ilmiah dalam pembelajaran jarak jauh berbasis masalah berbantuan edmodo. Desain penelitian ini yakni embended experimental. Subjek penelitian sebanyak 70 siswa kelas XI MIPA SMAN 2 Jember. Instrumen soal yang digunakan berupa 4 soal essay. Didapatkan nilai n-gain kelas eksperimen 0,795 (tinggi), kelas kontrol 0,313 (sedang). Sedangkan effect size kelas eksperimen 3,28 (kuat) dan kontrol  1 (cukup). Hal ini menunjukkan pembelajaran jarak jauh berbasis masalah berbantuan edmodo berpengaruh kuat terhadap kemampuan penalaran ilmiah siswa pada materi gelombang.